PENGARUH KERAGAMAN PRODUK, PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PT SERAYA MAKMUR PERDANA - NOVRY, NOVRY; Nainggolan,S.E.,M.SI., Nora Pitri (SCIENTIA JOURNAL, 2021)
This research aims to examine and analyze the effect of product diversity, promotion and product quality on purchasing decisions at PT Seraya Makmur Perdana. The data was collected by distributing questionnaires with a sample size of 140 respondents and using a Full screen feature. The research data used is statistical data in the form of multiple comparison line tests. The t test results show the value of product diversity 239> 3.204 with sig 0.002 <0.05 means that product diversity has a significant effect on purchasing decisions, the promotional value of 0.249> 3.066 with sig 0.002 <0.05 means that promotion Decisions and prices have a major influence on purchases product quality is 0.266> 3.175 with sig 0.002 <0.05 This means that high-quality products have a negative impact on purchasing decisions. While the F test results show the value of 125,663> 9,978 with sig 0,000 <0.05, so that simultaneously the variables of product diversity, promotion and product quality significant influence on purchasing decisions.